Decidualized Endometrioma: Its Sonography and Optimal Clinical Management. (March 2022) - Fernandez, Carlos M.; Levine, Elliot M.; Sodini, Irma; Pena, Maria; Shuber, Heider; Elliott, Stephanie
Endometriosis is a condition which affects many reproductive age women. During pregnancy, an ovarian endometrioma may undergo decidualization, which may take on the sonographic appearance suggestive of malignancy. In this instance, a surgical approach for treatment may be deemed necessary. Three cases are presented with different outcomes, worthy of viewing the contrasting management. In case 1, a patient was diagnosed with a left ovarian cyst at her routine 20-week gestation sonogram. This sonographic examination was suggestive of an ovarian malignancy. The patient underwent laparoscopy with left salpingo-oophorectomy at 23 weeks gestational age, without complications. The pathologic diagnosis of the removed mass was a decidualized endometrioma. In case 2, a female patient presented with bilateral ovarian decidualized endometriomas that were demonstrated sonographically and had the appearance of malignancy. This patient was treated conservatively with serial follow-up sonograms during her pregnancy. At the 2-month post-partum follow-up sonogram demonstrated persistent bilateral endometriomas, without decidualization. However, in case 3, possible decidualization of an endometrioma was seen, and a follow-up sonogram revealed the presence of ovarian carcinoma. There is previously published support for watchful waiting when similar sonographic findings, in pregnancy, are seen.